Family restrictions at work - Enriqueta Aragonés (Economies, 2024)
This paper analyzes one of the causes of the current gender-unbalanced situation in the labor market: the discrimination that individuals face at work due to their commitment to unpaid care work. It aims at finding mechanisms that may induce a change from the current unbalanced situation to a world in which males and females are found in more equal shares in all professions and at all levels. I construct a formal model that includes the heterogeneity of individuals regarding their family commitments and I investigate how it affects the individual's optimal labor market participation. The welfare of individuals with commitment to family duties is reduced for two different reasons: for not being able to participate as much in the labor market and thus receive a lower labor income and for not being able to contribute as much to their family commitments. I compare the results for the female and male sections of the society and I illustrate the observed gender gaps in terms of labor market participation, income levels, and the overall utility obtained. I find that even though the gender wage gap may be alleviated with reductions in the cost associated to unpaid care work, the gender utility gap will persist.
Keywords: J7; J31; 330; discrimination; labor market; unpaid care work